Gambling‐related cognitive distortions predict level of function among US veterans seeking treatment for gambling disorders. (19th February 2018) - Shirk, Steven D.; Kelly, Megan M.; Kraus, Shane W.; Potenza, Marc N.; Pugh, Kendra; Waltrous, Christopher; Federman, Edward; Krebs, Christopher; Drebing, Charles E.
Abstract : Background and Objectives: Gambling Disorder (GD) is characterized by recurrent gambling behavior that is associated with significant impairment and distress, high psychiatric comorbidities, and high functional disability. The military veteran population appears particularly susceptible to developing the disorder, but relatively little has been studied among this population. The purpose of the present study is to investigate the clinical psychopathologies and comorbidities of veterans seeking treatment for problem gambling and how problem gambling may impact functioning. Methods: Treatment‐seeking veterans meeting criteria for GD ( N  = 61) underwent a structured clinical interview and completed the South Oaks Gambling Screen (SOGS), the Gambling Symptom Assessment Scale (G‐SAS), the Yale‐Brown Obsessive‐Compulsive Scale for Gambling Disorder (PG‐YBOCS), the Gambling Belief Questionnaire (GBQ), the Barratt Impulsiveness Scale (BIS‐11), and the Sheehan Disability Scale (SDS). Results: Veterans seeking treatment for GD had high rates of psychiatric and addiction disorder comorbidities. Few veterans had previously sought treatment and most reported substantive challenges in social and occupational functioning. When determining how gambling‐related characteristics (ie, severity and cognitive distortions) impact function, severity of cognitive distortions was the strongest statistical predictor of overall functional disability. Conclusions and Scientific Significance: The findings from this study indicate that there is high comorbidity between GD and other psychiatric and addictive disorders, as well as social and occupational functioning. In addition, cognitive distortions related to gambling relate importantly to overall functioning and should be considered in the development of interventions for veterans with GD. (Am J Addict 2018;27:108–115)